Malaria epidemiology, surveillance and response for elimination in Lao PDR - Chawarat Rotejanaprasert; Vilayvone Malaphone; Mayfong Mayxay; Keobouphaphone Chindavongsa; Virasack Banouvong; Boualam Khamlome; Phoutnalong Vilay; Viengxay Vanisavaeth; Richard J Maude (BMC, 2024)
Abstract Background Lao PDR has made significant progress in malaria control. The National Strategic Plans outline ambitious targets, aiming for the elimination of Plasmodium falciparum and P. vivax malaria from all northern provinces by 2025 and national elimination by 2030. This article presents an overview of malaria epidemiology, surveillance, and response systems in Lao PDR, emphasizing experiences and achievements in transmission reduction. Methods Data on surveillance, monitoring and evaluation systems, human resources, infrastructure, and community malaria knowledge during 2010-2020 were systematically gathered from the national program and relevant documents. The collected information was synthesized, and discussions on challenges and future prospects were provided. Results Malaria control and elimination activities in Lao PDR were implemented at various levels, with a focus on health facility catchment areas. There has been significant progress in reducing malaria transmission throughout the country. Targeted interventions, such as case management, vector control, and community engagement, using stratification of control interventions by catchment areas have contributed to the decline in malaria cases. In elimination areas, active surveillance strategies, including case and foci investigation, are implemented to identify and stop transmission. The surveillance system has facilitated timely detection and response to malaria cases, enabling these targeted interventions in higher-risk areas. Conclusions The malaria surveillance and response system in Lao PDR has played a crucial role in reducing transmission and advancing the country towards elimination. Challenges such as importation, drug resistance, and sustaining support require ongoing efforts. Further strengthening surveillance, improving access to services, and addressing transmission determinants are key areas of focus to achieve malaria elimination and enhance population health in Lao PDR.